Who participates in communal violence? Survey evidence from South Africa - Christopher Claassen (Research & Politics, 2014)
Little is known about the thousands of people who take part in communal violence. Existing research is largely based on interviews, impressionistic accounts and government records of arrestees. In contrast, this paper examines data from a novel survey of a representative sample of residents of Alexandra, a township in South Africa where a 2008 nation-wide wave of anti-immigrant riots began. Data on participation in the attacks were collected using a method ensuring the privacy of responses, thus potentially reducing response bias. In contrast to the conclusions of existing research, which emphasize the participation of young males, the survey data reveal that a significant number of participants were female and participants were not particularly young, being 34 years old on average. Participants are more likely to support an opposition party, attend community policing meetings and have a high-school education.